2014
DOI: 10.1002/chem.201403703
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Substituted 2‐Methyl‐1,4‐Naphthoquinones: Redox Behavior Predictions

Abstract: In the context of the investigation of drug-induced oxidative stress in parasitic cells, electrochemical properties of a focused library of polysubstituted menadione derivatives were studied by cyclic voltammetry. These values were used, together with compatible measurements from literature (quinones and related compounds), to build and evaluate a predictive structure-redox potential model (quantitative structure-property relationship, QSPR). Able to provide an online evaluation (through Web interface) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 88 publications
2
31
0
Order By: Relevance
“…In this section, we describe the electrochemical properties of the 3‐benz(o)ylmenadiones to evaluate the influence of the benzyl substitution. We previously evaluated the substitution effects on the menadione core (i.e., the western region of the 3‐benz(o)ylmenadione derivatives) and found that the two one‐electron transfers were sensitive to the nature of the substituent and the position of substitution . The redox potentials of the substituted 3‐benz(o)ylmenadiones (Table and Figures S3–S42) were measured by CV (Table ) and SWV (Table S3) at 25 °C using a glassy carbon electrode in DMSO solvent and tetra‐ n ‐butylammonium hexafluorophosphate [N( n Bu) 4 PF 6 ] as the supporting electrolyte.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we describe the electrochemical properties of the 3‐benz(o)ylmenadiones to evaluate the influence of the benzyl substitution. We previously evaluated the substitution effects on the menadione core (i.e., the western region of the 3‐benz(o)ylmenadione derivatives) and found that the two one‐electron transfers were sensitive to the nature of the substituent and the position of substitution . The redox potentials of the substituted 3‐benz(o)ylmenadiones (Table and Figures S3–S42) were measured by CV (Table ) and SWV (Table S3) at 25 °C using a glassy carbon electrode in DMSO solvent and tetra‐ n ‐butylammonium hexafluorophosphate [N( n Bu) 4 PF 6 ] as the supporting electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a model based on simpler molecular descriptors is desirable. Recently, our group has reported the possibilities of QSPR modeling for prediction of the redox potential of substituted 2‐methyl‐1,4‐naphthoquinones (menadiones) . An online evaluation model was built and made available to predict the electrochemical properties of these quinones and redox‐active analogues to aid medicinal chemists in targeting their synthetic efforts toward redox‐active agents.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient synthetic methodologies have been established (4,5) and will allow preparation of a large array of diverse benzylmenadiones for further structureactivity relationship investigations. Already developed chemoinformatic tools are available for predicting the redox potentials of polysubstituted menadiones (6,7). Application of these tools to the polysubstituted benz(o)ylmenadiones will be instrumental in predicting their oxidant character and other molecular descriptors in order to guide synthetic efforts toward analogues with desired properties (7).…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of plasmodione is achieved in only one step from cheap commercially available starting materials, and its low-molecular-weight structure provides a large chemical space for optimization by derivatization (3). Its structure served as a starting point for development of chemical optimization strategies aimed at generating benzylmenadione derivatives with superior pharmacokinetic or pharmacodynamic properties (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Nonetheless, non-conducting films are typically formed by a few units of impermeable dimers or oligomers, subsequently producing few electroactive sites [9,10], such as in the dimerization of aniline [11][12][13], phenol [14][15][16] and quinones [17][18][19]. In this letter, we report the successful electrochemical synthesis of a conductive dapsone polymer using cyclic voltammetry in a lower potential window and high scan rates.…”
Section: Introductionmentioning
confidence: 99%